Identify Melatonin as a Novel Therapeutic Reagent in the Treatment of 1-Bromopropane(1-BP) Intoxication. Issue 3 (January 2016) - Xu, Yongpeng; Wang, Shuo; Jiang, Lulu; Wang, Hui; Yang, Yilin; Li, Ming; Wang, Xujing; Zhao, Xiulan; Xie, Keqin
Abstract : Abstract: 1-Bromopropane (1-BP) has been used as an alternative for fluoride compounds and 1-BP intoxication may involve lung, liver, and central neural system (CNS). Our previous studies showed that 1-BP impaired memory ability by compromising antioxidant cellular defenses. Melatonin is a powerful endogenous antioxidant, and the objective of this study was to explore the therapeutic role of melatonin in the treatment of 1-BP intoxication. Rats were intragastrically treated with 1-BP with or without melatonin, and then sacrificed on 27th day after 1-BP administration. The Morris water maze (MWM) test was used to evaluate the spatial learning and memory ability of the experimental animals, and NeuN staining was performed to assess neuron loss in hippocampus. We found that rats treated with 1-BP spent more time and swam longer distance before landing on the hidden platform with a comparable swimming speed, which was markedly mitigated by the pretreatment with melatonin in a concentration-dependent manner. In addition, 1-BP-induced notable decrease in neuron population in hippocampus by promoting apoptosis, and melatonin pretreatment attenuated those changes in brain. The GSH/GSSG ratio was proportionately decreased and heme oxygenase 1 was increased in the rats exposed to 1-BP (Figure 6), and administration of melatonin restored them. Meanwhile, MDA, the level of lipid peroxidation product, was significantly increased upon exposed to 1-BP, which was significantly attenuated by melatonin pretreatment, indicating that administration of 1-BP could interfere with redox homeostasis of brain in rat, and such 1-BP-induced biomedical changes were reversed by treatment with melatonin. We conclude that treatment with melatonin attenuates 1-BP-induced CNS toxicity through its ROS scavenging effect.